2012
DOI: 10.1007/s10661-012-2877-5
|View full text |Cite
|
Sign up to set email alerts
|

Assessment and monitoring of long-term forest cover changes in Odisha, India using remote sensing and GIS

Abstract: Deforestation and fragmentation are important concerns in managing and conserving tropical forests and have global significance. In the Indian context, in the last one century, the forests have undergone significant changes due to several policies undertaken by government as well as increased population pressure. The present study has brought out spatiotemporal changes in forest cover and variation in forest type in the state of Odisha (Orissa), India, during the last 75 years period. The mapping for the perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
32
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 71 publications
(35 citation statements)
references
References 24 publications
0
32
0
2
Order By: Relevance
“…In particular, information obtained from landscape metrics can be very valuable for the improvement of silvicultural prescriptions and baselines for forest management, as well as to highlight effects of implemented actions (Sano et al, 2009;Reddy et al, 2013;Costa et al, 2014;Paliwal and Mathur, 2014).…”
Section: T Simoniello Et Al: Land Cover Changes and Forest Landscapmentioning
confidence: 99%
“…In particular, information obtained from landscape metrics can be very valuable for the improvement of silvicultural prescriptions and baselines for forest management, as well as to highlight effects of implemented actions (Sano et al, 2009;Reddy et al, 2013;Costa et al, 2014;Paliwal and Mathur, 2014).…”
Section: T Simoniello Et Al: Land Cover Changes and Forest Landscapmentioning
confidence: 99%
“…2). Deforestation in the study area started mainly after independence of India because of infrastructure development, construction of dams and population pressure (Reddy ., 2013a). Encroachment on forest lands and converting them in to cultivated area by shifting cultivation played a significant role in deforestation for the period I (Dash, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The review analysed the gross and net deforestation rates and sum up the Government initiatives for conservation of forests in India (Reddy et al, 2013a). Reddy et al, (2013b) studied long term forest cover change over Odisha, India and observed that information on historical changes in Indian forests is scarce. Harikrishna et al (2014) has spatially explicitly mapped the forest cover change in Andhra Pradesh and found large scale deforestation during period.…”
Section: Introductionmentioning
confidence: 99%